노인의 사회적 배제가 심리적복지감에 미치는 영향에서 사회적 지지의 매개효과 - 박선아(Sun-Ah Park); 정효미(Hyo-Mi Jeong); 차명화(Myung-Hwa Cha) (한국콘텐츠학회 논문지, 18(3), 2018)
The purpose of this study was to examine the influence of the social exclusion factor of elderly people in a local community on their psychological wellbeing and whether or not social support would perform a mediating role in the relationship between social exclusion factor and psychological wellbeing. The subjects in this study were the elderly people who registered with a senior welfare center located in North Jeolla Province. The findings of the study were as follows: First, the social exclusion factor and social support factor of the elderly people were found to have exerted a statistically significant influence on psychological wellbeing. Second, the social support factor was found to have had partial mediating effects on the relationship between the social exclusion factor and psychological wellbeing. The findings of the study illustrated that the social support factor played a buffering role in the social exclusion factor that affected the psychological wellbeing of the elderly people. 본 연구는 지역사회 거주 노인들의 사회적 배제 요인이 심리적복지감에 어떠한 영향을 미치는지를 알아보고, 사회적배제 요인과 심리적복지감 사이에 사회적 지지가 매개역할을 하는지를 검증하는데 목적이 있다. 본 연구를 위해 전라북도 소재 노인복지관에 등록되어 있는 노인을 대상으로 구조화된 설문지를 통해 자료를 수집하였으며, 260명의 설문내용으로 연구한 결과는 다음과 같다. 첫째, 노인의 사회적 배제 요인과 사회적지지 요인은 심리적복지감에 통계적으로 유의미한 영향을 미치는 것으로 나타났다. 둘째, 사회적지지 요인이 사회적배제 요인과 심리적복지감 간에 부분매개효과 있는 것으로 나타났다. 종합적인 연구결과 사회적지지 요인은 노인의 심리적복지감에 영향을 미치는 사회적 배제 요인에 대해 완충역할을 하고 있는 것으로 나타났으며, 사회 배제적 상황에 놓여 있는 노인이라 할지라도 가족을 포함하여 이웃, 지역사로부터 사회적지지가 이루어진다면 심리적복지감이 유지될 수 있다는 것을 알 수 있는 결과이다.